A sodium laser guide star coupling efficiency measurement method. (September 2016) - Feng, Lu; Shen, Zhi-Xia; Xue, Suijian; Li, Yang-Peng; Jin, Kai; Otarola, Angel; Bo, Yong; Zuo, Jun-Wei; Bian, Qi; Wei, Kai; Hu, Jing-Yao
Abstract: A large telescope's adaptive optics (AO) system requires one or more bright artificial laser guide stars to improve its sky coverage. The recent advent of a high power sodium laser is perfect for such application. However, besides the output power, other parameters of the laser also have a significant impact on the brightness of the generated sodium laser guide star, mostly in non-linear relationships. When tuning and optimizing these parameters it is necessary to tune based on a laser guide star generation performance metric. Although return photon fluxis widely used, variability of the atmosphere and sodium layer makes it difficult to compare results from different sites or even within a short time period for the same site. A new metric, coupling efficiency, is adopted in our field tests. In this paper, we will introduce our method for measuring the coupling efficiency of a 20W class pulse sodium laser for AO application during field tests that were conducted during 2013–2015.